INFORMATION RETRIEVAL PADA RESEP MASAKAN MENGGUNAKAN METODE CBR ( CASE BASED REASONING ) MELALUI FACEBOOK MESSENGE (Information Technology and Telematics, 2014)
Abstract - Indonesia is a rich country in culinary. Recipes needed as a medium that can assist in preparing food ingredients to the presentation. There are still many people who are looking for recipes information via the web, no one has been through social networking sites.The use of social networking sites as a medium of social interaction one of which is "Facebook". Facebook has a chat application called Facebook Messenger. The method used is the method of CBR (Case Based Reasoning) is a method to build an expert system decision-making of the new cases based on the solution of the previous cases.Authors build system recipes by utilizing social networking ie facebook messenger. This system was developed with the Java programming language with Netbeans editor, SQL Server 2008 database and social media facebook. With a view to overcome the problems associated with finding information about recipes that are new to the user. From the test results of the system that performed the acquisition of relevant data to get the results, which reached 90%.Keywords: Information Retrieval, Recipes, Facebook Messenger, Java, SQL Server Abstrak - Indonesia merupakan negara yang kaya akan kulinernya.. Resep masakan dibutuhkan sebagai suatu media yang dapat membantu dalam menyiapkan bahan-bahan masakan sampai penyajian. Masih banyak orang yang mencari informasi resep masakan melalui web, belum ada yang melalui situs jejaring sosial.Penggunaan situs jejaring sosial sebagai media interaksi sosial salah satunya adalah “Facebook” . Facebook mempunyai aplikasi chat yang diberi nama Facebook Messenger. Metode yang digunakan adalah metode CBR ( Case Based Reasoning) merupakan metode untuk membangun sistem pakar dengan pengambilan keputusan dari kasus yang baru berdasarkan solusi dari kasus-kasus sebelumnya.Penulis membangun sistem resep masakan dengan memanfaatkan jejaring sosial yaitu facebook messenger. Sistem ini dikembangkan dengan bahasa pemrograman Java dengan editor Netbeans, database SQL Server 2008 dan media sosial facebook. Dengan maksud untuk mengatasi masalah yang berhubungan dengan pencarian informasi tentang resep masakan kepada user yang masih awam. Dari uji coba sistem yang dilakukan hasil perolehan data yang relevan mendapatkan hasil yang mencapai 90%.Kata Kunci : Information Retrieval, CBR, Resep Masakan, Facebook Messenger, Java, SQL Server